Influence of latent toxoplasmosis on the secondary sex ratio in mice - KAŇKOVÁ, Š.; KODYM, P.; FRYNTA, D.; VAVŘINOVÁ, R.; KUBĚNA, A.; FLEGR, J. (Parasitology, 2007)
The sex ratio may be influenced by many factors, such as stress and immunosuppression, age of parents, parity and sex of preceding siblings. In animal systems, parasitism often changes the sex ratio of infected hosts, which can increase the probability of their transmission. The most common human protozoan parasite in developed countries, Toxoplasma gondii (prevalence 20%−80%), is known to change the behaviour of its intermediate hosts, thereby increasing the probability of transmission to its definitive host (the cat) by predation. The intermediate hosts, which under natural conditions are rodents, serve as the vector for Toxoplasma. Therefore, we speculate that Toxoplasma can alter the secondary sex ratio (i.e. male to female ratio in the offspring) of infected females to increase the proportion of (congenitally infected) male offspring, which are the more migratory sex in most rodent species. Here we studied the sex ratio of experimentally infected laboratory mice, expressed here as the proportion of males in the litter. In accordance with our hypothesis and results of previous retrospective cohort studies on human subjects, mice with toxoplasmosis produced a higher sex ratio than controls, in the early phase of latent infection. In the later phase of infection, mice with congenital toxoplasmosis had a lower sex ratio than controls, which is in accord with the Trivers-Willard hypothesis of sex ratio manipulation, suggesting that females in poor physical condition give birth to more female offspring.